2021
DOI: 10.1097/yco.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning, artificial intelligence and the prediction of dementia

Abstract: Purpose of reviewArtificial intelligence and its division machine learning are emerging technologies that are increasingly applied in medicine. Artificial intelligence facilitates automatization of analytical modelling and contributes to prediction, diagnostics and treatment of diseases. This article presents an overview of the application of artificial intelligence in dementia research. Recent findingsMachine learning and its branch Deep Learning are widely used in research to support in diagnosis and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
0
14
0
4
Order By: Relevance
“…b) Implicit Detection of Neurological Disorders: Patterns of impairment in natural language production (e.g., writing samples, spoken language) have proven sensitive to detecting a wide range of neurological and psychiatric disorders (Garrard et al, 2005). Automated screening using implicit language sampling is emerging a powerful tool for early detection of prodromal dementia (Merkin et al, 2022;Song et al, 2011;Spooner et al, 2020). We know of no current algorithm that considers abnormal semantic distance as a predictor of cognitive impairment.…”
Section: Potential Applications and Future Directionsmentioning
confidence: 99%
“…b) Implicit Detection of Neurological Disorders: Patterns of impairment in natural language production (e.g., writing samples, spoken language) have proven sensitive to detecting a wide range of neurological and psychiatric disorders (Garrard et al, 2005). Automated screening using implicit language sampling is emerging a powerful tool for early detection of prodromal dementia (Merkin et al, 2022;Song et al, 2011;Spooner et al, 2020). We know of no current algorithm that considers abnormal semantic distance as a predictor of cognitive impairment.…”
Section: Potential Applications and Future Directionsmentioning
confidence: 99%
“…According to the literature, a ML device has been used to identify, forecast, and predict certain diseases and calamities, including SARS-CoV-2 (Chamola et al 2021 ; Caballé-Cervigón et al 2020 ; Merkin et al 2022 ; Rahimi et al 2021 ). To appropriately assess the transmission of the pandemic, Harrow and coauthors built a presumption data-driven approach, as shown in Figure S2 .…”
Section: Significant Applications Of ML For the Covid-19 Pandemicmentioning
confidence: 99%
“…Patients with dementia will benefit from high-quality care when these diverse and strategic resources are utilized effectively. Therefore, ML is a crucial component in achieving this goal, and there is evidence that ML knowledge from clinical data can be used to plan care for people at risk of different dementia forms [ 27 , 28 , 29 , 30 , 31 ]. Review articles on the use of AI in the brain sciences analyze the opportunities and challenges associated with its implementation [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%